Simulating a Community Mental Health Service During the COVID-19 Pandemic: Effects of Clinician–Clinician Encounters, Clinician–Patient–Family Encounters, Symptom-Triggered Protective Behaviour, and Household Clustering - Cardinal, Rudolf N.; Meiser-Stedman, Caroline E.; Christmas, David M.; Price, Annabel C.; Denman, Chess; Underwood, Benjamin R.; Chen, Shanquan; Banerjee, Soumya; White, Simon R.; Su, Li; Ford, Tamsin J.; Chamberlain, Samuel R.; et al. (Frontiers in Psychiatry, 2021)
OBJECTIVES. Face-to-face healthcare, including psychiatric provision, must continue despite reduced interpersonal contact during the COVID-19 (SARS-CoV-2 coronavirus) pandemic. Community-based services might use domiciliary visits, consultations in healthcare settings, or remote consultations. Services might also alter direct contact between clinicians. We examined the effects of appointment types and clinician–clinician encounters upon infection rates. DESIGN. Computer simulation. METHODS. We modelled a COVID-19-like disease in a hypothetical community healthcare team, their patients, and patients’ household contacts (family). In one condition, clinicians met patients and briefly met family (e.g. home visit or collateral history). In another, patients attended alone (e.g. clinic visit), segregated from each other. In another, face-to-face contact was eliminated (e.g. videoconferencing). We also varied clinician–clinician contact; baseline and ongoing “external” infection rates; whether overt symptoms reduced transmission risk behaviourally (e.g. via personal protective equipment, PPE); and household clustering. RESULTS. Service organization had minimal effects on whole-population infection under our assumptions but materially affected clinician infection. Appointment type and inter-clinician contact had greater effects at low external infection rates and without a behavioural symptom response. Clustering magnified the effect of appointment type. We discuss infection control and other factors affecting appointment choice and team organization. CONCLUSIONS. Distancing between clinicians can have significant effects on team infection. Loss of clinicians to infection likely has an adverse impact on care, not modelled here. Appointments must account for clinical necessity as well as infection control. Interventions to reduce transmission risk can synergize, arguing for maximal distancing and behavioural measures (e.g. PPE) consistent with safe care.